Understanding Physics - Jakeways, Robin (Physics education, 1998)
There are many books on the market now that cover the material in a typical first-year University Physics course. They mostly originate in the USA where introductory College Physics is clearly big business, and in general they are of an excellent standard. A number of departments, including my own, use one of these as an all-embracing first-year text. Not the least of the reasons for this is financial since it is much cheaper for the students than purchasing a text for each topic. When I learnt of a competitor originating on this side of the Atlantic I was cheered and admired the bravery of an attempt to enter such a competitive market. The book is claimed to be suitable for a student with no background in physics so it has to fulfil this claim as well as offer something a little special if it is going to compete in the publishing jungle. Let's start with an apparently crude comparison. To the student it does not look anywhere near as daunting at first sight as do some of its competitors. For example, the book that we use contains 1500 pages and weighs about eight pounds (OK, 3.6 kg if you insist). Mansfield and O'Sullivan is both shorter and lighter by a factor of two. As a consequence it is much more efficiently packed with information but loses nothing in clarity of exposition - the winner so far! Apart from this there are several reasons why I quite like it and a few odd places where I find it difficult to raise even one cheer. One aspect that appeals to me is that the authors develop the subject in a refreshingly new fashion. Most other texts start with several hundred pages of Mechanics and work steadily through via Thermal Physics, Electricity and Magnetism and so on, to finish with Modern Physics. Mansfield and O'Sullivan have different ideas. They start conventionally with several chapters on Mechanics, in which are wrapped SHM, fields and orbits, all nicely brought together. A quite remarkable omission here is any mention or discussion of forced harmonic motion and resonance. Immediately following these is a nice exposition of Special Relativity which, logically, is exactly where it should be since it can really no longer be described as `modern'! On the way, and throughout the book, they introduce a number of mathematical tools in shaded boxes, one example being differentiation from scratch on page 19, which is presumably aimed at the beginner. A chapter on Mechanical Properties of Materials is followed by Thermal Physics, which goes as far some of the more exotic thermodynamic functions and the Maxwell - Boltzmann distribution. The next chapter, on Wave Motion, is quite good on waves in general but is very thin on optical matters. Lenses and mirrors are discussed in four pages or so but there is no mention of optical instruments. Interference and diffraction are nicely treated and the phasor method is used to good effect but one looks in vain for anything about interference by division of amplitude, e.g. thin films. There is one very peculiar oddity concerning diffraction at a slit which I cannot help remarking upon. It is said that, since the equation predicting the position of the first subsidiary maximum has no solution when the slit size is smaller than the wavelength, then under those conditions `diffraction is not observed'. What is the student to think? Does no light at all pass through the slit or does it go straight through without spreading? At this point Quantum Mechanics is introduced. As with Special Relativity, this seems to me to be the right place for it since it, too, can no longer be described as modern and all the necessary groundwork has been covered. It is not at all easy going, especially for those students with no prior background in physics, but that is a reflection of the topic rather than the style. Having got over this novelty we then meet a chapter on Electric Currents followed by one on Electric Fields - to my mind a much friendlier approach for the student than the conventional approach, which is the other way around. We then come to Magnetic Fields and here the treatment is quite bizarre and idiosyncratic. The subject is developed via the concept of the magnetic pole, which seems to me to be going back in time. As Feynman says: `` It is therefore nicer from a physical point of view to describe things realistically in terms of the atomic currents rather than in terms of a density of some mythical `magnetic poles'.'' The consequence of this approach is that the H field is considered to be the primary (magnetic) field and B only appears later - as soon as real life problems are met! Now to me and, I am sure, the great majority of physicists, a magnetic field is essentially defined in nature and quantity by the expression , i.e. the basic physics is the force on a moving charge. Why then cloud the issue with a non-existent entity and a field that is not very useful at this level of physics? Another consequence is that the term `magnetic field' is reserved for H whereas modern usage inclines very much more to using it to describe B. This could be a source of confusion for students who might consult different texts. After this, matters follow a normal course. Electromagnetic Induction is followed by Maxwell's Equations, which are discussed using the full panoply of D, E, H and B rather than the more economical E and B. A chapter on Atomic Physics starts with Bohr theory and continues with a full quantum mechanical treatment of the hydrogen atom. This is quite tough going but clearly set out. The next chapter is entitled Electrons in Solids and contains, inter alia, quite a lot about semiconductor devices of all kinds. The final chapter covers the essentials of nuclear physics, including the quark model, and concludes with a quick run-down on the physics of stars, `Life, the Universe and Everything'. My overall impression, even after some detailed criticisms, is favourable. The writing style is a little heavy and could be described as old-fashioned but it is clear and relatively economical with words. A very useful appendix contains a summary of `Mathematical Rules and Formulae', which is always handy to have in such an all-embracing book. One very good feature of many books of this nature is the provision of copious examples. The present book provides only a very modest number (with answers to all of them - a definite plus point). It seems a little odd that it refers continually to the fact that a further selection may be found in Halliday, Resnick and Walker, which is one of its competitors! In conclusion it has to be said that the overall approach is mathematically somewhat more formal than most other texts; this is at a time when the mathematical fluency of students entering university, even with good grades in Mathematics, is sinking fast. I have no objections to this since there is always a danger of gradually simplifying a subject to the detriment of rigour and clarity but it makes it less easy to browse through. The book will provide a good backup to a course of lectures, and students will generally find it a useful reference which will keep them on the straight and narrow (except for the magnetic poles!). It certainly includes more material than can reasonably be covered in a first-year course, bearing in mind the background of today's A-level students, but that is no bad thing since it will provide continuity with material met in later years.